2017
DOI: 10.1159/000486676
|View full text |Cite
|
Sign up to set email alerts
|

Low Discontinuation Rate of Infliximab Treatment in Steroid-Dependent/Refractory Crohn’s Disease Patients

Abstract: Background: Many patients with moderate to severe Crohn’s disease (CD) are treated with infliximab (IFX). As most of these patients experience a long-lasting therapy, the outcome and withdrawal of IFX treatment are important clinical questions. Methods: In this retrospective study, we analyzed the treatment outcome in moderate to severe CD patients with a steroid-dependent/refractory disease course started on IFX. Withdrawal of IFX was evaluated in patients with deep remission defined as clinical (Harvey-Brads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 36 publications
0
11
0
2
Order By: Relevance
“…In our study the same rate was achieved after only 9 months, and patients were treated for the same period of time. Another study has shown that half of the CD patients were in remission 17 months after the end of therapy [13]. The differences could be caused by another definition of remission (clinical/endoscopic, with or without the use of immunomodulators).…”
Section: Discussionmentioning
confidence: 99%
“…In our study the same rate was achieved after only 9 months, and patients were treated for the same period of time. Another study has shown that half of the CD patients were in remission 17 months after the end of therapy [13]. The differences could be caused by another definition of remission (clinical/endoscopic, with or without the use of immunomodulators).…”
Section: Discussionmentioning
confidence: 99%
“…Application of the exclusion criteria yielded fteen studies (9 manuscripts, 6 conference abstracts), encompassing a total of 1,212 patients (Table 1). [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] A diagnosis of CD was captured for 769 patients, and a diagnosis of UC was provided for 443 patients. 18,20,21 Nine studies were prospective in design, 16,18,19,21,23,24,[27][28][29] and seven were carried out at multiple institutions.…”
Section: Search Resultsmentioning
confidence: 99%
“…Two studies de ned deep remission (DR) beyond the minimum criteria of clinical remission and endoscopic remission -Magro 2016 included histologic remission de ned as a Geboe's score < 4, and Kaymak 2018 supplemented both histologic remission and two years of biochemical remission (fecal calprotectin < 150). 22,24 Two conference abstracts used the same cohort and reported rates of DR at different time points, therefore this cohort was only counted one time. 27,28 Ten studies featured only in iximab (IFX), 16, 18, 20-22, 24, 26-29 two used only adalimumab (ADA), 19,23 one study assessed golimumab, 30 and two studies incorporated both IFX and ADA.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations